2007
DOI: 10.1007/s10551-006-9322-z
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Relationship Between Personal Values and Moral Reasoning of Undergraduate Business Students

Abstract: business undergraduate majors, cognitive moral development, defining issues test-2, maintains norms, personal interest, personal values, post-conventional, schwarts values questionnairc, value types,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 20 publications
4
67
0
Order By: Relevance
“…A universal definition regarding human values is not found in the literature (Lan, Gowing, McManhon, Rieger, & King, 2008).…”
Section: Human Values and Schwartz's Value Theorymentioning
confidence: 99%
“…A universal definition regarding human values is not found in the literature (Lan, Gowing, McManhon, Rieger, & King, 2008).…”
Section: Human Values and Schwartz's Value Theorymentioning
confidence: 99%
“…Various defi nitions of CSR Source: Mcwilliams et al, 2006;Meehan et al, 2006;Leitão and Silva, 2007. Besides traditional Confucian values, emerging market values also impact on contemporary Chinese value structures (Whitcomb et al, 1998;Redfern and Crawford, 2004). The transition to a market-based economy in China since 1978 has led to changes, and contemporary Chinese values refl ect a mixed structure which can be divided into the following three orientations: (1) Chinese traditional values, displaying strong Confucian dynamism and long-term orientation; (2) western values, represented by individualism and materialism; and (3) a combination of Chinese traditional values and imported western values, including communism and collectivism (Chung et al, 2008;Lan et al, 2008).…”
Section: Pyramid Of Csrmentioning
confidence: 99%
“…Wong et al (2009) found that Chinese students are more tolerant of accepting of making facilitating payments to get things moving. According to Lan et al (2008), western values represented by individualism and materialism have a great infl uence on Chinese youth. In their study, Chinese accounting students ranked self-respect, capable, social recognition, and pleasure as the top values.…”
Section: Pyramid Of Csrmentioning
confidence: 99%
“…[1] Wood and Jones (1995) suggested three roles of stakeholders to justify the importance of stakeholders, evaluation on CSR: (1) stakeholders are the source of expectations of CSR, (2) stakeholders experience the effects of CSR, and (3) stakeholders will make evaluation on CSR. Therefore, many scholars have applied the stakeholder approach to running their empirical studies, such as [19], [16], [20], [21], [22].…”
Section: Stakeholder Theory and Csrmentioning
confidence: 99%